Skin conductance algesimetry for monitoring postoperative procedural pain in infants—a pilot study - Matthias Nissen; Anna Romanova; Ralf-Bodo Tröbs (PAIN Reports)
Abstract. Introduction:. Pain assessment in the nonverbal infant is challenging and its detection and treatment is of significant importance considering the associated short- and long-term neurologic sequelae. Objectives:. We aimed to evaluate the effectiveness of continuous noninvasive skin conductance algesimetry (SCA), reflecting the sympathetic nervous system's stress response, compared with other referent pain surrogates during nociceptive heel lance/squeeze (HLS) events in infants after routine surgery. Methods:. Data were prospectively collected on 20 infants during the postoperative period, and HLS events were compared with non-nociceptive control events. Skin conductance algesimetry monitoring was performed in addition to behavioral (Children's and Infants' Postoperative Pain Scale [CHIPPS]) and physiological measures. Results:. During nociceptive HLS events, heart rate (HR), CHIPPS, and the SCA-derived parameter skin conductance fluctuations (SCF) were increased and SCF was positively correlated with CHIPPS. Performance accuracy for differentiation of HLS from non-nociceptive events was high for CHIPPS and moderate for SCF and HR. In regression analysis, only CHIPPS contributed significantly to predicting HLS events. Conclusion:. CHIPPS showed superior ability over SCF and HR in detecting HLS events in infants. A multimodal use of SCA combined with a behavioral assessment might constitute an important step toward improved detection and treatment of pain in this fragile cohort.